Knowledge, Attitude, and Practice of Complementary and Alternative Medicine among Program’s Residents in Tabuk, Saudi Arabia - Alqahtani, Talal Saeed; Khalil, Tahani Ahmed; Alharbi, Asma Ali; Alnomasi, Waad Saad; Alnomasi, Mohammed Saad; Althwab, Saeed Mubarak; Jaser, Amani Abu; Alshahrani, Rahaf Saud (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Complementary and alternative medicine (CAM) focuses on stimulating the body’s ability to heal itself through energy alignment, herbal supplementation, and other balancing techniques. AIM: The objective of the study was to investigate and compare the Knowledge Attitude Practice (KAP) of CAM among program’s residents in Tabuk region. METHODS: A cross-sectional CAP study was conducted among program’s residents in Tabuk region. All program’s residents of all specialties in Tabuk region were included in the study. Data were collected by predesigned electronic questionnaire covering the needed items. Collected data were coded and analyzed using SPSS Inc., Chicago, Illinois, USA. The Chi-square test was used as a test of significance and p = 0.05 or less was considered statistically significant. RESULTS: Most (95.8%) of the participants have heard about CAM, 25% have used CAM in treatment before, and 72.3% of them reported beneficial outcome, 25.7% strongly agree and 48.6% agree that CAM is a useful complement to pharmacological medicine, 38.2% believed that the results of CAM are usually due to the placebo effect, and 52.1% recommended using CAM. On the other hand, 79.9% have knowledge about acupuncture, 54.9% spiritual healing and herbal medicine, 43.1% massage, 41% yoga, 70.8% bloodletting cupping, and 56.3% about cauterization. More than third (38.2%) of the participants agreed that the use of herbal products is a valid form of drugs which can be used for the treatment of variety of diseases, 48.6% agreed that CAM is a useful complement to pharmacological medicine, while 36.1% strongly agreed that CAM treatments are not tested in a scientifically recognized manner. CONCLUSION: In our study, the majority of program’s residents in Tabuk region agree that CAM is a useful complement to pharmacological medicine and recommended using CAM while reasonable percentage of them believed that the results of CAM are usually due to the placebo effect.